Global supply chain relationship, local market competition, and suppliers’ innovation in developing economies - Ding, Lei; Atallah, Gamal; Sun, Guoqiang (Technological and Economic Development of Economy, 2022)
This article examines how suppliers’ innovation in developing countries is affected by the interaction of vertical global supply chain relationships and horizontal market competition structure. We devised a bidirectional dynamic game model consisting of competing suppliers in a developing economy and an overseas buyer in a developed economy for innovation decision process in a suppliers cluster. Our research shows that global supply chain relationship is the primary factor to influence local cluster innovation and profit. Total innovation of the cluster is proved to be greater in global supply relationship with a powerful buyer than a non-powerful buyer. However, suppliers in a powerful buyer chain are not able to capture the value they created from innovation. Local competition structure plays its secondary role on cluster innovation through interaction with vertical chain relationship. Based on prior innovation research on either vertical supply chain power dynamics or horizontal competition intenseness, our study contributes as the first to employ a theoretical suppliers’ innovation model for an integrative analysis encompassing both global and local power dynamics.First published online 03 December 2021